2021
DOI: 10.1038/s41467-021-22394-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficient photocatalytic hydrogen peroxide generation coupled with selective benzylamine oxidation over defective ZrS3 nanobelts

Abstract: Photocatalytic hydrogen peroxide (H2O2) generation represents a promising approach for artificial photosynthesis. However, the sluggish half-reaction of water oxidation significantly limits the efficiency of H2O2 generation. Here, a benzylamine oxidation with more favorable thermodynamics is employed as the half-reaction to couple with H2O2 generation in water by using defective zirconium trisulfide (ZrS3) nanobelts as a photocatalyst. The ZrS3 nanobelts with disulfide (S22−) and sulfide anion (S2−) vacancies … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(41 citation statements)
references
References 63 publications
1
40
0
Order By: Relevance
“…coli . Moreover, by choosing a more suitable ED, such as benzylamine, people can not only prepare H 2 O 2 but also obtain a value-added chemical . Therefore, PHP with the ED is a promising research field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…coli . Moreover, by choosing a more suitable ED, such as benzylamine, people can not only prepare H 2 O 2 but also obtain a value-added chemical . Therefore, PHP with the ED is a promising research field.…”
Section: Resultsmentioning
confidence: 99%
“…Among numerous photocatalysts, carbon nitride (CN) has become a research hotspot in recent years due to its low price and excellent performance. For example, Choi and co-workers achieved a millimolar level of H 2 O 2 production per hour in the presence of ethanol using CN modified with heteroatom dopants as the photocatalyst and successfully applied it to the disinfection of Escherichia coli . Moreover, using benzylamine as the ED, Tian et al not only prepared H 2 O 2 but also obtained a value-added chemical, benzonitrile, which further demonstrated the huge potential of photoproduction of H 2 O 2 with an ED in practical applications . Nowadays, the research of PHP with the assistance of an ED is making considerable progress, ,,,, and the reported yield is still increasing. …”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of nitriles from the selective oxidation of amines plays a key role in both laboratory and industrial synthetic processes because nitrile is an important intermediate product for the synthesis of several fine chemicals, pharmaceuticals and agrochemicals [167][168][169][170][171][172][173] . The photocatalytic oxidation of amines to nitriles is an effective approach for the synthesis of nitriles under mild conditions (Equation 16).…”
Section: Reduction Of O 2 Coupled With Oxidation Of Benzylaminementioning
confidence: 99%
“…Another representative study by the Chen and Han group reported that ZrS 3 nanoribbons (NBs) containing disulfide (S 2 2− ) vacancies and sulfide anion (S 2− ) vacancies as a photocatalyst exhibited good photocatalytic performance for the formation of H 2 O 2 and simultaneously selective conversion of benzylamine to benzonitrile, and the selectivity exceeded 99% ( Tian et al, 2021 ). Similarly, they demonstrated that S 2 2− vacancies in ZrS 3 NBs accelerated the separation of photo-induced carriers, hole extraction, and kinetics of benzylamine oxidation.…”
Section: Surficial Vacanciesmentioning
confidence: 99%